2019
DOI: 10.5755/j01.itc.48.1.19066
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Modified Delay-Based Control Algorithm with an Experimental Application

Abstract: In the present article, a new modified delay-based control structure is proposed to improve the closed-loop performance of control systems. The controller is designed for a second-order linear time-invariant system. The controller parameters are tuned by using the integral of the absolute error criterion. Theoretical results are simulated and experimentally applied to an electromechanical system, which is identified with an interactive system identification tool. It is shown that the present controller provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…In general, the method of IAE, ISE, ITSE, and ITEA are often used to evaluate PID controller design performance in the literature [11], [13], [36]- [38]. Instead of evaluating these error criterias as only objective, Zwe-Lee Gaing's study demonstrated that the aim of the combinations of these error criterias, which include weight factors, is a better way to form a common objective [11].…”
Section: Objective Functionsmentioning
confidence: 99%
“…In general, the method of IAE, ISE, ITSE, and ITEA are often used to evaluate PID controller design performance in the literature [11], [13], [36]- [38]. Instead of evaluating these error criterias as only objective, Zwe-Lee Gaing's study demonstrated that the aim of the combinations of these error criterias, which include weight factors, is a better way to form a common objective [11].…”
Section: Objective Functionsmentioning
confidence: 99%
“…Nowadays, various methods of technological process control are being developed, e.g., [42,44]. The MPC controller is conceived as multidimensional, i.e., it works in a coordinated manner with a higher number of manipulated variables (MVs) and controlled variables, i.e., measured outputs (MOs) what is typical in MIMO or MISO systems.…”
Section: Model Predictive Controlmentioning
confidence: 99%